KALIGRAFI ARAB AYAT AL-QURAN TENTANG PERGANTIAN SIANG DAN MALAM DALAM SENI LUKIS BATIK - YUNITA LIDYA, Drs. Syafei, M.Ag. (Serupa The Journal of Art Education, 2019)
The creation of this final work aims to visualize Arabic calligraphy verses of the Koran about the day and night battles in batik painting. The work brought several verses of the Koran that explain the changing of day and night. The embodiment method of this final work goes through five stages: preparation, elaboration, synthesis, concept realization, and completion. Author Successfully Realizing 10 works with the title: moon, dawn, sun, succession, night continuously, day continues to continue, change, the greatness of God, protection, livelihood.Keywords: Arabic Calligraphy, Day and Night, Batik Painting